O06.4 Efficacy and cost-effectiveness of qHPV vaccine with imiquimod or podophyllotoxin for patients with anogenital warts (HIPvac). (14th July 2019) - Gilson, Richard; Bennett, Kate; Sandmann, Frank; Murray, Macey; Doré, Caroline; Haddow, Lewis; Nugent, Diarmuid; Lacey, Charles; Jit, Mark; Soldan, Kate; Caverly, Emilia; Nathan, Mayura; et al.
Abstract : Background: The comparative efficacy, and cost-effectiveness, of imiquimod (IMIQ) or podophyllotoxin (PDX) cream, either alone or in combination with the quadrivalent HPV vaccine (Gardasil®, Merck) in the treatment and prevention of recurrence of anogenital warts is unknown. Methods: A randomised, controlled, multi-centre, partially-blinded factorial trial with an economic evaluation. Participants had new or recurrent warts; not treated within 3 months; no qHPV-vaccination. Randomisation, stratified by gender, previous warts, HIV status to IMIQ 5% (16W), or PDX 0.15% cream (4W, extended to 16W if warts persist). Simultaneous blinded randomisation to Gardasil® or saline control (0–2–6 months). Composite primary outcome of wart clearance at 16W and remaining clear to 48W; analysis by logistic regression with multiple imputation for missing follow-up values. Economic evaluation considered the costs per quality-adjusted life year (QALY) for the National Health Service in England. Results: 503 participants enrolled; mean age 31 years; 66% male (20% of males MSM); 50% previous warts; 2% known HIV+. Adjusted OR (95%CI) for IMIQ relative to PDX 0.81 (0.54, 1.23); vaccine relative to placebo 1.46 (0.97, 2.20). aOR for primary outcome components (same comparators) of wart-free at W16 0.77 (0.52, 1.14) and 1.30 (0.89, 1.91) and remaining wart-free at 48W (in those wart-free at W16) 0.98 (0.54, 1.78) and 1.39 (0.73, 2.63) respectively. PDX without qHPV vaccine had the highest probability of being cost-effective across willingness-to-pay thresholds of GBP0–50, 000/QALY. Adding qHPV vaccine to PDX exceeded GBP80, 000/QALY. Conclusion: Though the effect of vaccine was not statistically significant, the odds of clearance at 16W+48W (primary outcome) were 46% higher with vaccine, consistent with the effects seen in component outcomes, wart-free at 16W, and 48W. IMIQ and PDX had similar efficacy; there was no evidence of a lower recurrence with IMIQ. PDX without qHPV vaccine is likely most cost-effective at the current qHPV price, but addition of qHPV may become cost-effective with reduced pricing. Disclosure: No significant relationships.